Hybrid active and passive local shimming (HAPLS) for two‐region MRI. Issue 4 (28th November 2022) - Ren, Zhi Hua; Stockmann, Jason; Dewdney, Andrew; Lee, Ray F.
Abstract : Purpose: An MRI scanner is equipped with global shim systems for shimming one region of interest (ROI) only. However, it often fails to reach state‐of‐the‐art when shimming two isolated regions of interest simultaneously, even though the two‐area shimming can be essential in scan scenarios, such as bilateral breasts or dyadic brains. To address these challenges, a hybrid active and passive local shimming technique is proposed to simultaneously shim two isolated region‐of‐interest areas within the whole FOV. Methods: A local passive shimming system is constructed by optimized bilateral ferromagnetic chip arrays to compensate for the magnet's significant high‐order B0 inhomogeneities at the boundary of the manufacturer's specified homogeneous volume, thus locally improving the available FOV. The local active shimming consists of 40‐channel DC loops powered by 64‐channel current amplifiers. With the optimized current distribution, active shimming can correct the residual low‐order B0 inhomogeneities and subject‐specific field inhomogeneities. In addition, active shimming is used to homogenize the center frequencies of the two regions. Results: With the implementation of the hybrid active and passive local shimming, the 95% peak‐to‐peak was reduced from 1.92 to 1.12 ppm by 41.7%, and RMS decreased from 0.473 to 0.255 ppm by 46.1% in a two‐phantom experiment. The volume ratio containing MR voxels within a 0.5‐ppm frequency span increased from 64.3% to 81.3% by 26.3%. Conclusion: The proposed hybrid active and passive local shimming technique uses both passive and active local shimming, and it can efficiently shim two areas simultaneously, which is an unmet need for a commercial MRI scanner.